Introducing physical telerehabilitation in seniors with mobility limitation: System feasibility and acceptance - Wood, Jeffrey; Finkelstein, Mark; Cha, Eunme; Finkelstein, Joseph (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Physical therapy has been shown effective in geriatric population in addressing mobility limitation. Telerehabilitation systems may support physical therapy programs at patient homes however such systems were not systematically assessed in seniors. The Home Automated Telemanagement (HAT) system for in-home physical telerehabilitation of seniors with mobility limitations was developed and tested. The HAT rehabilitation system was designed to allow patients with mobility limitations to complete an individualized physical therapy plan prescribed by a physical therapist and to allow for clinicians to monitor and assist with in-home rehabilitation. We conducted a 12-week study to assess the feasibility and patient acceptance of the system. Our results showed that home-based physical telerehabilitation is feasible in seniors with mobility limitations, and it can potentially improve patient functional status significantly. Statistically significant improvement was documented using Berg Balance Scale (change from 36.6 ± 12.1 to 41.7 ± 11.1, p<;0.004), Timed 25-foot Walk (change from 13.5 ± 8.6 to 10.6 ± 4.5, p<;0.04), and 6-minute walk (change from 36.6 ± 12.1 to 41.7 ± 11.1, p<;0.004). The participants of the study demonstrated a very high level of support for the home-based physical telerehabilitation program.